Historical Transformations of Ukrainian Ritual Culture in an Urban Environment (1920s – Early Twenty-First Century) - Bekh, Kateryna (Український історичний журнал, 2021)
The aim of the article is analyzing and elucidating the main transformations and changes in the components of the Ukrainian ritual culture in urbanized environment. The research methodology is based on general scientific (analysis, synthesis, generalization), special (comparative historical, problem-chronological), source study methods, as well as the method of direct observation. The scientific novelty consists in analyzing significant modifications and revealing the trends in components’ transformation of the traditional Ukrainians’ culture in urbanized environment. It has been mentioned, that peculiar attention has to be paid to the city as a center of culture, which constantly develops; here spiritual value and ethnical orientations of city dwellers are formed and synthesized. First of all, attention was paid to the development, existence and modification of family rituality and its marriage and wedding component as one of the most important ethnic identification indicators and the element of ethnicity preservation. The main factors of transformational ritual practices and decreasing the traditional rituality components during different periods of social, political and globalization processes were elucidated. The main results and conclusions. It has been noted that during the 1920s – 1980s the Soviet power played considerable role in the transformation of spiritual foundations of the Ukrainian people. In particular, the creation of a new family was socially significant and it was under the state authorities’ control, which was especially manifested in cities. During the mentioned period, the standardization and unification of the ritual wedding ceremony took place, which considerably affected the loss of many of its components, considerably narrowing its national color, high esthetics of song culture and theatrical performances. Instead, the end of the 20 – early of the 21 centuries is characterized by intensive globalization. It has been determined that wide using of innovative technical means of communication as one of the important factors caused significant transformations of the Ukrainians’ ethnic culture. Modern family rituality of city dwellers, marriage-wedding, in particular, on the one hand, is characterized by variability and diversity, and on the other hand, by reactivation of traditional rites, phenomena, and attributes.